2010
DOI: 10.2478/v10042-008-0085-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 mRNA expressions along with in vitro differentiation of hepatocyte precursor cells from fetal, young and old rats.

Abstract: Non-differentiated cells are attractive targets for cell therapy. During liver regeneration oval cells intensively proliferate and differentiate extending their metabolic activity. Hepatic cytochromes P450 (CYPs) can be linked either with metabolic activation of toxic compounds or drug metabolism. We investigated the differentiation and biotransformative potential of non-differentiated cells in primary cell cultures isolated from livers of fetuses (16-days-old), young (4-monthsold) and old (20-months-old) rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Since the initial cloning and characterization of HGF as a mitogen for hepatocytes [40], increasing studies have revealed that hepatic differentiation and maturation of cells occurs upon exposure to HGF [18], [19], [41], [42]. In addition to HGF, DMSO can be used to induce hepatic differentiation [20]. However, when separately used, the effects of hepatic induction by these two molecules are not satisfying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the initial cloning and characterization of HGF as a mitogen for hepatocytes [40], increasing studies have revealed that hepatic differentiation and maturation of cells occurs upon exposure to HGF [18], [19], [41], [42]. In addition to HGF, DMSO can be used to induce hepatic differentiation [20]. However, when separately used, the effects of hepatic induction by these two molecules are not satisfying.…”
Section: Discussionmentioning
confidence: 99%
“…Although FLSPCs can be largely amplified by soft agar culture, because they are immature and lack function, they have to differentiate into hepatocytes to restore normal liver functioning. Therefore, in this study by combining the hepatic differentiation inducers HGF [17][19] with dimethyl sulfoxide (DMSO) [20], [21], we successfully induced the differentiation of FLSPCs into hepatocyte-like cells. Thus, this effective strategy could provide quality assurance for treating liver diseases.…”
Section: Introductionmentioning
confidence: 99%
“…(Salmin et al 2017) CYP3A1 is higher in cells from young rats than in old rats. (Czekaj et al 2010) CYP3A in the liver are sensitive to aging with 50-70% decreases, while CYP3A in the intestine is unchanged and in the kidney increased. (Warrington et al 2004) Generally speaking, hepatic CYP3A enzymes are decreased with age.…”
Section: P450-3 Familymentioning
confidence: 99%
“…For example, CYPs expression can be affected by hormones (Daskalopoulos et al 2012), cytokines (Kot & Daujat-Chavanieu 2018), pregnancy, (He et al 2005) sex, (Agrawal & Shapiro 2003;Das et al 2014) and age. CYPs are subjected to agedependent changes in cell differentiation (Czekaj et al 2010) and epigenetic regulation, (Li et al 2009) and age-related metabolic syndrome, (Bondarenko et al 2016) kidney diseases, (Velenosi et al 2012) diabetes, (Park et al 2016) nonalcoholic steatohepatitis, (Li et al 2017) virus hepatitis, and cirrhosis. (Kirby et al 1996) Age of animals greatly affects drug metabolism, (Durnas et al 1990) alters pharmacokinetics of xenobiotics, (Matalova et al 2016;Shi & Klotz 2011) and thus alters the sensitivity to drugs and toxicants such as acetaminophen, (Mach et al 2014) isoniazid, (Mach et al 2016) aflatoxin B1, (Kirby et al 1996;Wang et al 2018) and thioacetamide.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired glucose tolerance, however, is neither specific nor sensitive for ageing. Cytochrome p450 (CYP) mRNA expression has been found experimentally to correlate highly with age, with CYP1A2, CYP2B1/2 and CYP3A1 all increased and CYP2E1 decreased in young hepatocyte proliferation in the condition of hepatocarcinogenesis . While this may lead to further advances in the difference in function between young and old livers, it is not yet conceivable that these could be markers to aid in the usability of a potential donor organ and remain firmly as a scientific model.…”
Section: Telomeresmentioning
confidence: 99%